Microelectromechanical Systems 2002
DOI: 10.1115/imece2002-33321
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of an Electro-Thermally Driven Long-Stretch Micro Drive With Cascaded Structure

Abstract: A single micro actuator usually can provide only limited output force and displacement. Therefore, proper integration of several basic actuators into an arrayed structure becomes an attractive way to magnify the output. Here an electro-thermally driven large-stretch micro drive (LSMD) with cascaded compliant structure and compact size (about 2000μm ×500μm) is designed and analyzed. Two kinds of materials, polysilicon and electroplated nickel, are used in finite element simulations. From simulations, several de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…After implementation of a motion amplifier, the maximum output force dropped to 3 mN while the maximum displacement increased only to 20 mm (Lai et al, 2004). The simulation results of the cascaded 'V ' shaped EDTAs using polysilicon and nickel reported by Hsu et al (2002) showed larger displacements, typically >100 and 250 mm with 10 and 0.5 V, respectively. Therefore, the trade-off between output displacement and the force depends primarily on the design, kinematics, and material properties of the microactuator.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…After implementation of a motion amplifier, the maximum output force dropped to 3 mN while the maximum displacement increased only to 20 mm (Lai et al, 2004). The simulation results of the cascaded 'V ' shaped EDTAs using polysilicon and nickel reported by Hsu et al (2002) showed larger displacements, typically >100 and 250 mm with 10 and 0.5 V, respectively. Therefore, the trade-off between output displacement and the force depends primarily on the design, kinematics, and material properties of the microactuator.…”
Section: Introductionmentioning
confidence: 93%
“…The geometrical dimensions of all the design elements are listed in Table 1. The actuator design is based on a multi-cascaded approach (Bordatchev et al, 2002;Hsu et al, 2002;Bordatchev and Nikumb, 2004) and consists of a pair of identical, in-plane, cascaded structures linked together at the top by a horizontal beam as motion platform. Each cascaded structure is formed by a serial connection of several basic actuation units which magnify the output in-plane displacements.…”
Section: Microactuator Designmentioning
confidence: 99%
“…This is a monolithic structure which does not require post-machining assembly. The design is based on a multicascaded approach 16,17 and consists of a pair of identical cascaded actuation structures ͑microactuators͒ oriented in a face-to-face direction to act as microtweezers. Tweeze jaws are supported by vertical levers with fixed ends ͑anchor 2͒ to hold the object.…”
Section: Introductionmentioning
confidence: 99%
“…Ideal microgripper performance requires quasi-static motions to grasp and hold an object that may be inappropriate for the electrostatic actuators, which are more suitable for generating vibrating motions. Electrothermally driven actuators [10][11][12][13][14][15][16][17] are more compact, can provide higher output force and larger displacements, but geometrically are more complex in nature. Actuation motions are generated by application of an electric potential to the conducting elastic material ͑usually metal͒ to produce Joule heating ͑resistive heating͒ resulting in thermal expansion of the entire structure.…”
Section: Introductionmentioning
confidence: 99%
“…They have the displacement/force outputs typically higher than other micro-actuators, and should be easier to control [1,2]. However, mainly due to relatively high temperatures of the operating regimes [3,4], any analytical predictions and numerical simulations are rather challenging. Several parameters to characterize three different physical environments involved, i.e.…”
Section: Introductionmentioning
confidence: 99%